2007
DOI: 10.1016/j.jinorgbio.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and spectroscopy of model molybdopterin complexes

Abstract: The preparation and characterization of new model complexes for the molybdenum cofactor are reported. The new models are distinctive for the inclusion of pterin-substituted dithiolene chelates and have the formulation Tp*MoX(pterin-R-dithiolene) (Tp* = tris(3,5,-dimethylpyrazolyl)borate), X= O, S, R= aryl or −C(OH)(CH 3 ) 2 ). Syntheses of Mo(4+) and (5+) complexes of two pterin-dithiolene derivatives as both oxo and sulfido compounds, and improved syntheses for pterinyl alkynes and [Et 4 N][Tp*Mo IV (S)S 4 ] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 58 publications
(56 reference statements)
1
63
0
Order By: Relevance
“…Our strategy for exploring the possibilities created by a Mo-pterin-dithiolene partnership has been to develop the reaction chemistry of pterin- and quinoxaline-substituted dithiolene complexes of molybdenum to serve as small molecule analogues for studying the effects of these N-heterocycles on dithiolene properties. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Our strategy for exploring the possibilities created by a Mo-pterin-dithiolene partnership has been to develop the reaction chemistry of pterin- and quinoxaline-substituted dithiolene complexes of molybdenum to serve as small molecule analogues for studying the effects of these N-heterocycles on dithiolene properties. 27 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cPMP, dihydropterins are characterized by a high sensitivity to oxygen with half-lives of minutes [29] while tetrahydropterins such as biopterin are more stable at physiological pH (t 1/2 = 10-20 min) [30]. Studies with different synthetic pyranopterins demonstrated a remarkable increase in stability of pyranopterins in comparison to dihydro and tetrahydropterins [31,32], which fits much better with the observed stability of cPMP. The chemical structure of cPMP was clarified using high resolution mass spectrometry and 1 H NMR spectroscopy [33].…”
Section: Chemical Properties and Structure Of Cpmpmentioning
confidence: 63%
“…24 Surprisingly, the Magnetic Circular Dichroism and Electron Paramagnetic Resonance spectra exhibited by Tp*MoO(bdt) and Tp*MoO(pterin-dithiolene) complexes have nearly identical parameters suggesting the pterin substituent has little effect on the molybdenum environment. 24 …”
Section: Pterin-dithiolene Models Of Mocomentioning
confidence: 97%
“…65 A notable piece of data from this study is the 95,97 Mo hyperfine value, whose small value (11 G) was interpreted as consistent with a highly covalent Mo-(pterin-dithiolene) system with a HOMO based on the C and S atoms of the dithiolene. 24, 66 …”
Section: Pterin-dithiolene Models Of Mocomentioning
confidence: 99%
See 1 more Smart Citation